Providing High-Quality Professional Learning Opportunities Through a Lesson Study Conference - Dotger, Sharon; Whisher-Hehl, Jessica; Heckathorn, Jennifer; Moquin, F. Kevin (Innovations in Science Teacher Education, 2021)
We report on the development and implementation of a conference designed to highlight the Next Generation Science Standards (NGSS Lead States, 2013) using lesson study as an effective professional-development practice for inservice teachers. The purpose of this article is to highlight details from the development and implementation that can be used by others wishing to replicate the conference. First, we give an overview of the practice of lesson study and explain how it was used by one of four lesson study teams that taught their research lesson publicly at the conference in front of 80 observers. Then, we describe a sample research proposal and share specific information about the processes used to coach the lesson study teams and plan the conference, and we share conference agendas and diagrams of lesson implementations to support readers’ visualization of the implementation. Finally, we conclude with three planning components that were vital to our ability to execute the conference and link the design to existing lesson study literature.